Upland Xerophyte Communities of Valley Landscapes of the Upper Reaches of the Chanty-Argun River (Mountainous Chechnya, Eastern Caucasus) - Belous Viktor; Alikhadzhiev Magomed; Erzhapova Razet (BIO Web of Conferences, 2023)
The paper discusses the features of plant communities of the upland xerophyte complex of the valley landscape of the upper reaches of the Chanty-Argun River. Regularly repeating and interconnected with environmental factors phytocenoses of the Itum-Kalinsky semiarid basin are noted. The abundance of species, their distribution by elements of the lower and middle mountain relief and communities were determined by experts on the basis of field information. Peculiarities of mountain-steppe communities, factors of their spatial differentiation are revealed. The studied communities are rich in species and are of significant conservation interest. With our research, we sought to emphasize the regional specificity of the studied communities, due to geographical, ecological, cenotic, and historical features.